Accuracy of MRI for Assessment of Depth of Invasion and Cervical Lymph Node Metastasis in Tongue Carcinoma (Journal of Dentistry and Allied Science, 2025)
Background: Tongue carcinoma is one of the most aggressive malignancies of the oral cavity. Magnetic resonance imaging (MRI) is a very important and useful imaging modality to diagnose tongue carcinoma. In the latest, 8th edition of UICC cancer staging manual was modified by incorporating depth of invasion (DOI) in the T categorization of oral cavity cancer. Tongue carcinoma has a relatively unfavourable prognosis. And that is possibly due to the absence of a strong barrier to prevent tumor diffusion and the presence of a well developed lympho-vascular system that increases the risk of metastasis. Objective: To evaluate the accuracy of MRI in the assessment of depth of invasion and cervical lymph node metastasis in tongue carcinoma. Methodology: This cross-sectional study was conducted at the Department of Radiology and Imaging at BSMMU, Dhaka, from March 2021 to February 2023. A total of 30 patients with tongue carcinoma were enrolled after informed written consent. All patients were subjected to detailed history and thorough clinical examination along with magnetic resonance imaging and histopathological examination. Results: Mean age of the study patients was 51.83±8.13 (SD) years with male predominance (70% male and 30% female). Majority of the patients presented with painless non healing ulcer (50%) and lymphnode involvement occurred in 46.7% patients. In MRI it was found that 40% patients had stage T2 cancer and histopathologically it was found that, 90% had squamous cell carcinoma. The mean depth of tumor invasion was 10.16±5.07 mm in MRI, and 9.37±3.68 mm in histopathological examination. Taking cut-off value of depth of invasion